Does Customer Loyalty Meet Repurchase and Purchase Intention? - Hermawan, Eric; Vikaliana, Resista (inovator, 2023)
Consumer behavior in the current era of disruption varies greatly, to see this, of course, it is necessary to carry out further analysis and research on current consumer behavior. Indicators in looking at consumer behavior researchers take the variables of customer loyalty, repurchase, and purchase intention. The purpose of this paper is to examine the relationship between Customer Loyalty, Repurchase, and purchase intention. The researcher conducted a descriptive qualitative research method by obtaining data through the Google Scholar and Mendeley applications as references. The research results in this study are: 1) customer loyalty is related to consumer behavior, 2) repurchasing is related to consumer behavior, and 3) purchase intention is related to consumer behavior. This paper is still limited to studies on two scientific article databases (Google Scholar and Mendeley).